2023
DOI: 10.1093/nutrit/nuad013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pattern, food, and nutritional supplement effects on cognitive outcomes in mild cognitive impairment: a systematic review of previous reviews

Abstract: Context Nutritional interventions may benefit cognition in people with mild cognitive impairment (MCI). However, evidence is yet to be synthesized in a way that can inform recommendations for clinical and public health settings. Objective To systematically review evidence on the effect of dietary patterns, foods, and nutritional supplements on cognitive decline in individuals with MCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Therefore, the relevance of diet and its relationship with c-miRNA levels in MCI was not evident considering these results [93]. However, certain components of the diet have been associated with better cognitive function and reserve in MCI and AD patients, particularly folates and vitamin B 12 [97], although results show high heterogeneity, and the underlying mechanisms are not clear.…”
Section: Human Studiesmentioning
confidence: 92%
“…Therefore, the relevance of diet and its relationship with c-miRNA levels in MCI was not evident considering these results [93]. However, certain components of the diet have been associated with better cognitive function and reserve in MCI and AD patients, particularly folates and vitamin B 12 [97], although results show high heterogeneity, and the underlying mechanisms are not clear.…”
Section: Human Studiesmentioning
confidence: 92%
“…PNCDs share similar neuropathological mechanisms with Alzheimer's disease, where anesthesia and surgery can elevate the expression of beta-amyloid (Aβ), ultimately leading to cognitive impairments [90]. Gut microbiotasynthesized or food-derived B vitamins, such as pyridoxine (vitamin B6), folate (vitamin B9), and cobalamin (vitamin B12), have been shown to improve cognitive abilities in patients with mild cognitive impairment (MCI) [91]. Bacteria like Escherichia coli, Bacillus subtilis, and Salmonella spp.…”
Section: Microbial Metabolitesmentioning
confidence: 99%
“…Multiple types of intervention have been applied to these populations to reduce the decline of cognitive function, such as the Mediterranean diet and the ketogenic diet as well as the regulation of fatty acids, antioxidants, vitamins, and micronutrients [ 12 - 15 ]. Andrews et al [ 16 ] conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effect of dietary patterns, food, and nutritional supplements on cognitive function in individuals with MCI. The findings of this review demonstrated that few nutritional interventions convincingly improved the cognition of individuals with MCI [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Andrews et al [ 16 ] conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effect of dietary patterns, food, and nutritional supplements on cognitive function in individuals with MCI. The findings of this review demonstrated that few nutritional interventions convincingly improved the cognition of individuals with MCI [ 16 ]. Vlachos et al [ 17 ] conducted a systematic review and found folate, vitamin E, omega-3 fatty acids, and certain multinutrient formulations have shown some preliminary promising results [ 17 ].…”
Section: Introductionmentioning
confidence: 99%